Education trough art in the context of art education of a child at a younger school age - Ernest Zawada (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
The aim of the article is to indicate the essence and possibilities of educating through art children in grades 1-3 of primary school during visual art classes. In the study, the need to raise the level of competences of early childhood education teachers in terms of creating conditions for children to learn about and experience art directly has been emphasized. Aim of the research: The aim of the article is to show the educational values of art realized in the course of children's art education in grades 1-3 of primary school. State of knowledge: Raising a sensitivity to beauty and developing the ability to express and reproduce art using various methods and techniques was established as a pedagogical task of a teacher in the scope of visual arts education. The encounter with art is the basis of the process of discovering its values. Conclusion: The text emphasizes that raising a child through art is connected not only with the need to constantly expand knowledge in this area, but above all to motivate children's artistic creativity.